Peningkatan Motivasi dan Hasil Belajar pada Materi Puasa melalui Teknik Pisang Cabe pada Siswa Kelas V SDN Delegan 2 Prambanan Tahun Ajaran 2017/2018 - Ahmad Sahar (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to determine the application of cooperative learning of Pisang Cabe technique in improving motivation and results of material learning fasting students class V Elementary School Delegan 2 Prambanan year 2017/2018. This research is a class action research (PTK). Data collection techniques using participatory observation, questionnaire (poll), tests, and documentation. The results showed that the student's motivation increased on the I cycle of 60.57% increase in cycle II by 83.3%. The results of the study in the I cycle reached an average of 78.4 with the highest value of 95 and the lowest value of 60, with a proof of a proof of 76%, increased in the cycle II by an average of 87.2, with the highest value of 100 and the lowest 75 with a proof of proof of 100%. The results of this study showed that application of Pisang Cabe technique (Think with Spouse, Find and Share) is effective in improving motivation and learning outcomes of students on fasting material.